Sport as art, dance as sport - Jason Holt (Karolinum Press, 2017)
A standing debate in philosophy of sport concerns whether sport can count as art in some sense. But the debate is often conducted at cross purposes. Naysayers insist that no sport is an artform while proponents insist that certain sport performances count as artworks - but these are entirely consistent claims. Both sides make unwarranted assumptions: naysayers are purists about sport and art (no transaesthetic purposes) whereas proponents are tokenists about artforms. Naysayers admit that figure skating may count as art yet only in non-competitive contexts. Their burden is thus to explain why a routine (e.g., Torvill and Dean's 'Bolero') may count as art in a showcase but not at the Olympics. The debate is also inevitably framed in terms of whether sport counts as art, neglecting the equally viable question of whether art in some form (e.g., competitive dance) may also count as sport. I conclude in favour of an appropriately qualified sport-as-art thesis.